Development of a new method for assessing otolith function in mice using three-dimensional binocular analysis of the otolith-ocular reflex - Shotaro Harada (Nature Portfolio, 2021)
Abstract In the interaural direction, translational linear acceleration is loaded during lateral translational movement and gravitational acceleration is loaded during lateral tilting movement. These two types of acceleration induce eye movements via two kinds of otolith-ocular reflexes to compensate for movement and maintain clear vision: horizontal eye movement during translational movement, and torsional eye movement (torsion) during tilting movement. Although the two types of acceleration cannot be discriminated, the two otolith-ocular reflexes can distinguish them effectively. In the current study, we tested whether lateral-eyed mice exhibit both of these otolith-ocular reflexes. In addition, we propose a new index for assessing the otolith-ocular reflex in mice. During lateral translational movement, mice did not show appropriate horizontal eye movement, but exhibited unnecessary vertical torsion-like eye movement that compensated for the angle between the body axis and gravito-inertial acceleration (GIA; i.e., the sum of gravity and inertial force due to movement) by interpreting GIA as gravity. Using the new index (amplitude of vertical component of eye movement)/(angle between body axis and GIA), the mouse otolith-ocular reflex can be assessed without determining whether the otolith-ocular reflex is induced during translational movement or during tilting movement.